Percepciones de directivos, docentes y estudiantes de básica y media acerca del clima escolar en un colegio privado de la ciudad de Ibagué (Papeles, 2012)
This article presents the advance of a research study named “perceptions of teachers, students and administrators about school climate in a private school in Ibague” as its name implies, this research is done with the objective to know and analyze what perceptions this people have about the environment we live in this school, having into account the categories communication, work social environment, retribution and benefits, sense of belonging and motivation. This research is mixed (qualitative, and quantitative).The research sample is formed for fifty four students who are in fifth, seventh, ninth and eleventh grades, eight teachers and one administrator.
Keywords: school climate; communication; work social environment; retribution and benefits; sense of belonging and motivation